Neuromyelitis optica mimics the morphology of spinal cord tumors - Erol, İlknur and Özkale, Murat and Savaş, Tülin and Alkan, Özlem and Çekinmez, Melih and Erbay, Ayşe (The Turkish Journal of Pediatrics, 2016)
Neuromyelitis optica (NMO) is an autoimmune disorder of the central nervous system, that predominantly affects the spinal cord and the optic nerve. Its key features include transverse myelitis, commonly associated with extensive inflammation spanning three or more consecutive vertebral segments. Longitudinal extensive spinal cord lesions can also occur in systemic autoimmune diseases, infections, vascular and metabolic disorders, subsequent to irradiation, intramedullary tumors and paraneoplastic myelopathies. We present a case study of an 8-year-old girl seropositive for antibodies against the aquaporin 4 who displayed longitudinal extensive spinal cord lesions, that was initially misdiagnosed as an intramedullary tumor.